The impact of oil on the Iran-Iraq war 1988 - 1980 - Eyal Slman, Isahaq Ahmad (Journal of Humanities & Social Sciences, 2021)
This study covers an overview of Iraqi oil, Iranian oil, and Gulf oil, And the relationship of oil to Middle Eastern events, most notably the Gulf wars, focusing on the first Gulf War, or what is known as the Iraq-Iran War, which lasted eight years, but stopped suddenly.The study concluded that the 1973 crisis is the cause of the Iraq-Iran war, and that the entire Arab Gulf oil is the cause of the Gulf wars, the reason for the interruption of the Iraq-Iran war is also oil, when the war turned into what is known as the tanker war - that is, the tankers of oil.
Keywords: politics; the Arabian Gulf; oil